Beyond forty acres and a mule : African American landowning families since Reconstruction - Reid, Debra A., 1960-; Bennett, Evan P. (University Press of Florida, 2012)
The articles in this anthology deal with some of the most perplexing issues facing black farmers in the South. The authors make their most important contribution when they address the seemingly contradictory philosophies that emerged as African Americans acquired and protected their real property.